Vontade e formação em Friedrich Nietzsche - Martello, Dionei José (2022)
This thesis aims to understand the role of the will to power in Nietzsche and the possible relationships between this concept and the formative question of the human. In order to achieve this objective, the will to power is firstly analyzed as the force responsible for acting, lacking a purpose and a final ity, the structures of cognitive restriction and ethical direction being nothing more than human creations dependent on several factors. It starts, therefore, with the breakdown of the old homogenizing narratives, which for Nietzsche kept human beings unde r control and made their lives full of meaning, serving as a compass for the conduct of educational institutions, and seeks to understand the possibilities arising from this context. with regard to the formation of a free will and without “anchor points”. It is argued that this reading of the author helps to conceive a formative process that allows humans to live autonomously, enjoying their creativity and independence, without losing sight of the importance of passing on the legacy of past generations. To this end, a rigorous analysis of Nietzsche's texts is undertaken, especially those of maturity, such as Thus Spoke Zarathustra, Human Too Human, Will to Power, etc., with a view to finding elements that support a philosophical formative vision present in h is work. , even if not fully developed by him, as is the case of his reflections regarding the will to power. The present work intends to innovate precisely in the sense of making this connection between the will to power, one of the capital principles of Nietzsche's work, with the possible developments of such principle and the possible existing connections with the formative issue. In formative terms, the will to power would contribute mainly with regard to the development of an autonomous, critical, crea tive individual, equipped with a solid epistemological and cultural base, but capable of resisting the harassment of all types of ideology.